Journal of Russian Laser Research - Krokhin, Oleg N.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Journal of Russian Laser Research is based on research carried out under the auspices of the prestigious Lebedev Physical Institute of the Russian Academy of Sciences. The journal publishes original, high-quality articles that follow new developments in all areas of laser research, including: laser physics; laser interaction with matter; properties of laser beams; laser thermonuclear fusion; laser chemistry; quantum and nonlinear optics; optoelectronics; solid state, gas, liquid, chemical, and semiconductor lasers. All articles are peer-reviewed.
Keywords: Lasers; Photonics; Microwaves; Optical engineering; Optics, Lasers, Photonics, Optical Devices; Microwaves, RF and Optical Engineering